Investigating Altruism and Selfishness Through the Hypothetical Use of Superpowers. (July 2019) - Das-Friebel, Ahuti; Wadhwa, Nikita; Sanil, Merin; Kapoor, Hansika; V., Sharanya
Drawing from literature associating superheroes with altruism, this study examined whether ordinary individuals engaged in altruistic or selfish behavior when they were hypothetically given superpowers. Participants were presented with six superpowers—three positive (healing, invulnerability, and flight) and three negative (fear inducement, psychic persuasion, and poison generation). They indicated their desirability for each power, what they would use it for (social benefit, personal gain, social harm), and listed examples of such uses. Quantitative analyses ( n = 285) revealed that 94% of participants wished to possess a superpower, and majority indicated using powers for benefitting themselves than for altruistic purposes. Furthermore, while men wanted positive and negative powers more, women were more likely than men to use such powers for personal and social gain. Qualitative analyses of the uses of the powers ( n = 524) resulted in 16 themes of altruistic and selfish behavior. Results were analyzed within Pearce and Amato's model of helping behavior, which was used to classify altruistic behavior, and adapted to classify selfish behavior. In contrast to how superheroes behave, both sets of analyses revealed that participants would hypothetically use superpowers for selfish rather than altruistic purposes. Limitations and suggestions for future research are outlined.